Phraseological units as reflection of ethnic stereotypes in Spanish culture and professional activities - O. S. Chesnokova (Дискурс профессиональной коммуникации, 2020)
The purpose of the paper is to give an overview of phraseological means incorporating ethnic allusions in the framework of the Spanish world model as a whole and in professional activities in particular. The author proceeds from the premise that professional education of participants in international processes should attach critical importance to the awareness of the nation’s associative thinking, especially related to ethnic stereotypes, for ensuring successful interethnic relationships. The Spanish perception of their own, alongside others’, national character is exemplified by numerous ethnically coloured phraseological units. Special attention is paid to ethnically orientated idioms referring to various professional activities. The author also considers historically based motivation of ethnic allusions in the Spanish phraseology, semantic and evaluative features of the phraseological units in question.The following conclusions are made:– ethnically related allusions in the Spanish phraseological world model are distinguished by specific images and stereotypes which are determined by historical and cultural experience of native speakers;– in terms of structural modes, phraseological units with ethnonyms follow the universal patterns of set phrases ranging from word combinations to complete sentences;– evaluative connotations of such units do not always provide reliable testimony of the actual ethnic stereotypes; many ethnically coloured images in Spanish idioms look paradoxical rather than demonstrate the Spaniards’ true vision of a nation rooted in the objective background.